Traditional Ceramic Kiln Development Model - Amboro, Joko Lulut; Wahyuningsih, Novita; Nurcahyanti, Desy (2016)
The research is focused on the traditional ceramic kiln development model as an application of the local culture to improve the teaching/learning activity in ceramic firing technique. The object of the research was the traditional kiln model in the ceramic craft village of Bentangan, Wonosari Sub-district, Klaten Regency, and the traditional kiln model in Melikan village, Wedi Sub-district, Klaten Regency. The research activity was an effort to preserve creative industry-based local culture as well as to improve the model of traditional ceramic kiln development as an object of teaching/learning activity improvement for students in ceramic firing technique. Those two ceramic craft-based creative industry villages have optimally-developed potencies. One of them is the existing kiln development model. The specific target to gain in this research was the materialization of the traditional ceramic kiln development model as the application of the ceramic craft-based local culture in the teaching/learning activity improvement for the students on the ceramic firing technique. The research itself is a local culture application and additional instrument engineering in the form of traditional kiln development model. The methods applied in the research were observation, discussion, and operational work methods. Activities which were related to the research objects were, among others, direct observations on the ceramic firing technology in Bentangan village, Wonosari, Klaten and in Melikan village, Wedi, Klaten. Following the observations, a new design of the traditional ceramic kiln development model was designed